Levantamento das populações de callicebus coimbrai Kobayashi & Langguth, 1999 em fragmentos de Mata Atlântica no Sul do estado de Sergipe, Brasil - Chagas, Renata Rocha Déda (2009)
Coimbra-Filho s titi monkey (Callicebus coimbrai Kobayashi & Langguth, 1999) is an endangered, but poorly-known primate that inhabits remnants of the Atlantic Forest in the Brazilian states of Sergipe and Bahia (northern coast). The present study aimed to evaluate the effects of habitat fragmentation on the ecological characteristics and provide information on population density and size, and basic ecological characteristics of the species within the study area. These data were also collected for other local primate species. The survey took place at the Fazenda Trapsa in southern Sergipe, where two survey techniques were applied playbacks (in fragments of < 50 ha) and line transects (fragments > 50 ha). A total of 476.1 km of line transect was walked between april and october, 2008. Population density was estimated using the DISTANCE program and the Kelker method. Density was also calculated directly from group counts. A total of 12 groups were identified in the four large fragments surveyed. Groups of Cebus xanthosternos and Callithrix jacchus were also observed in all four fragments. The presence of Callicebus in the two smaller fragments was confirmed by playback. The overall density in the larger fragments was 12.6 individuals per km². Both DISTANCE and Kelker provided considerable over-estimates of density. The results of this study indicate the need for caution in the interpretation and comparison of density estimates in studies of titi monkeys, as well as re-emphasizing the efficiency of alternative methods for the surveying of populations in small fragments. Fazenda Trapsa appears to have a total population of around 50 titis, which may have a good chance of survival over the long term, especially if certain conservation measures are taken. The results of the study reinforce the need for the establishment of a reserve network, and the development of active metapopulation management strategies, in order to guarantee the long-term prospects for the survival of C. coimbrai.